Agents and Artificial Intelligence Third International Conference, ICAART 2011, Rome, Italy, January, 28-30, 2011. Revised Selected Papers - Filipe, Joaquim; Fred, Ana.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Agents and Artificial Intelligence, ICAART 2011, held in Rome, Italy, in January 2011. The 26 revised full papers presented together with two invited paper were carefully reviewed and selected from 367 submissions. The papers are organized in two topical sections on artificial intelligence and on agents.
Keywords: Computer science; Computer Communication Networks; Computer software; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Data Mining and Knowledge Discovery; Information Storage and Retrieval